Interprofessional collaboration in hospitals: a critical, broad-based review of the literature. Issue 4 (3rd July 2020) - Pomare, Chiara; Long, Janet C.; Churruca, Kate; Ellis, Louise A.; Braithwaite, Jeffrey
ABSTRACT: Interprofessional collaboration (IPC) is a common term applied in the healthcare literature, with suggestions it contributes to improved quality and safety of patient care across the globe. Despite worldwide implementation of models of IPC, past systematic or meta-reviews on this topic have concluded that the evidence is mixed. However, these reviews are yet to adequately consider the qualitative and mixed-methods literature on this topic. In this critical review, we synthesize the outcomes and key findings of IPC in hospitals, taking a broader approach by including diverse study designs. A total of 4, 776 abstracts were screened from three major databases (Medline, CINAHL, Embase). Thirty-four studies fulfilled inclusion criteria. Although outcomes and key findings (e.g., staff turnover, error rates) were mostly positive, there were inconsistencies in the results. The included studies reflected a variety of study designs and different methodological approaches. Overall, our review revealed moderate evidence that IPC can positively influence patient, staff and organizational factors in hospitals, and that inconsistent findings may be due to variation in context (e.g., the cohort of patients). Recommendations from the review are to incorporate qualitative- and mixed-methods approaches to studying IPC in healthcare and tailor evaluations of IPC outcomes specific to the context.